2020
DOI: 10.1177/1362361320919286
|View full text |Cite
|
Sign up to set email alerts
|

Autistic peer-to-peer information transfer is highly effective

Abstract: Effective information transfer requires social communication skills. As autism is clinically defined by social communication deficits, it may be expected that information transfer between autistic people would be particularly deficient. However, the Double Empathy theory would suggest that communication difficulties arise from a mismatch in neurotype; and thus information transfer between autistic people may be more successful than information transfer between an autistic and a non-autistic person. We investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(174 citation statements)
references
References 39 publications
4
142
0
4
Order By: Relevance
“…All participants took part in three experimental tasks using a diffusion chain method (Crompton et al, 2020b). This procedure involves a series of dyadic interactions in which an individual first observes a researcher complete a task, and then completed that task with a second participant.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants took part in three experimental tasks using a diffusion chain method (Crompton et al, 2020b). This procedure involves a series of dyadic interactions in which an individual first observes a researcher complete a task, and then completed that task with a second participant.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Participants did not meet before the first task started, and were isolated in separate rooms whilst they waited for their turn to take part in the study. The first dyadic task involved building a tower out of spaghetti and plasticine (Caldwell and Millen, 2008), the second involved sharing a fictional story (see Crompton et al, 2020b), and the third involved participants creating geometric animal shapes from a Rubiks Twist ( TM ). Each task took between 1 and 5 min, and participants interacted with each other freely while completing each task.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…due to school placement). This could be an interesting avenue for future play interventions, given recent ndings of enhanced communication between autistic/autistic pairs, compared to autistic/non-autistic pairs (Crompton et al, 2020) and calls for strengths-based approaches from autism research organisations internationally (Huntley et al, 2019) .…”
Section: Types Of Play-based Interventionsmentioning
confidence: 99%
“…Recent empirical work with autistic adults has shown that social interaction quality and positive perceptions are driven by relational factors to a greater degree than individual ones (Crompton et al, 2020;Morrison et al, 2020). For instance, autistic adults disclose more about themselves (Morrison et al, 2020), communicate more effectively, and establish better rapport (Crompton et al, 2020) when interacting with other autistic adults relative to NA adults. This suggests that relational compatibility, and not just individual characteristics, contribute to social interaction outcomes for autistic adults, but it remains unclear whether specific social abilities either individually or dyadically underlie this effect.…”
Section: Introductionmentioning
confidence: 99%